IGF1R deficiency in vascular smooth muscle cells impairs myogenic autoregulation and cognition in mice - Miller, Lauren R.; Bickel, Marisa A.; Tarantini, Stefano; Runion, Megan E.; Matacchiera, Zoe; Vance, Michaela L.; Hibbs, Clara; Vaden, Hannah; Nagykaldi, Domonkos; Martin, Teryn; Bullen, Elizabeth C.; Pinckard, Jessica; et al. (Frontiers in Aging Neuroscience, 2024)
Introduction Cerebrovascular pathologies contribute to cognitive decline during aging, leading to vascular cognitive impairment and dementia (VCID). Levels of circulating insulin-like growth factor 1 (IGF-1), a vasoprotective hormone, decrease during aging. Decreased circulating IGF-1 in animal models leads to the development of VCID-like symptoms, but the cellular mechanisms underlying IGF-1-deficiency associated pathologies in the aged cerebrovasculature remain poorly understood. Here, we test the hypothesis that vascular smooth muscle cells (VSMCs) play an integral part in mediating the vasoprotective effects of IGF-1. Methods We used a hypertension-based model of cerebrovascular dysfunction in mice with VSMC-specific IGF-1 receptor (Igf1r) deficiency and evaluated the development of cerebrovascular pathologies and cognitive dysfunction. Results VSMC-specific Igf1r deficiency led to impaired cerebral myogenic autoregulation, independent of blood pressure changes, which was also associated with impaired spatial learning and memory function as measured by radial arm water maze and impaired motor learning measured by rotarod. In contrast, VSMC-specific IGF-1 receptor knockdown did not lead to cerebral microvascular rarefaction. Discussion These studies suggest that VSMCs are key targets for IGF-1 in the context of cerebrovascular health, playing a role in vessel stability alongside other cells in the neurovascular unit, and that VSMC dysfunction in aging likely contributes to VCID.